In vitro transformation of chlorogenic acid by human gut microbiota. Issue 5 (23rd December 2013) - Tomas‐Barberan, Francisco; García‐Villalba, Rocío; Quartieri, Andrea; Raimondi, Stefano; Amaretti, Alberto; Leonardi, Alan; Rossi, Maddalena
<x xml:space="preserve">Abstract</x> Scope Chlorogenic acid (3‐O‐caffeoyl‐quinic acid, C‐QA), the caffeic ester of quinic acid, is one of the most abundant phenolic acids in Western diet. The majority of C‐QA escapes absorption in the small intestine and reaches the colon, where the resident microbiota transforms it into several metabolites. C‐QA conversion by the gut microbiota from nine subjects was compared to evaluate the variability of bacterial metabolism. It was investigated whether a potentially probiotic Bifidobacterium strain, capable of C‐QA hydrolysis, could affect C‐QA fate. Methods and results Bioconversion experiments exploiting the microbiota from diverse subjects revealed that C‐QA was metabolized through a succession of hydrogenation, dexydroxylation and ester hydrolysis, occurring in different order among the subjects. Transformation may proceed also through quinic acid residue breakdown, since caffeoyl‐glycerol intermediates were identified (HPLC‐MS/MS, Q‐TOF). All the pathways converged on 3‐(3‐hydroxyphenyl)‐propanoic acid, which was transformed to hydroxyphenyl‐ethanol and/or phenylacetic acid in few subjects. A strain of Bifidobacterium animalis able to hydrolyze C‐QA was added to microbiota cultures. It affected microbial composition but not to such an extent that C‐QA metabolism was modified. Conclusion A picture of the variability of microbiota C‐QA transformations among subjects is provided. The transformation route through caffeoyl‐glycerol intermediates is described for the first time.